Chondro-Osseous Metaplasia in Ependymoma: A Rare Histopathological Finding - Ali Alkhaibary; Fahd AlSufiani; Ali H. Alassiri; Makki Almuntashri; Salma Tarik Al Qutub (Hindawi Limited, 2020)
Ependymoma is a circumscribed glioma composed of uniform glial cells with bland nuclei in a fibrillary matrix. It is characterized by the presence of perivascular pseudorosettes. Unusual histopathological findings have rarely been reported in ependymomas, 0.5% of all diagnosed cases. Such unusual and exceedingly rare histological findings include osseous or chondroid metaplasia. To the best of our knowledge, only 15 cases of osseocartilaginous ependymomas have been reported in English literature. We report a 3-year-old boy who presented with ataxia, vomiting, and headache for three months. Radiological imaging revealed a posterior fossa lesion. Histopathological examination of the lesion confirmed a posterior fossa ependymoma with chondro-osseous metaplasia. The present case outlines the clinical presentation, histopathological findings, and outcome of chondro-osseous metaplasia in ependymomas. To date, the etiology of chondro-osseous metaplasia in ependymomas remains uncertain. Further research exploring such phenomenon is of paramount importance to explain how these tumors develop.